TRENDS IN THE DEVELOPMENT AND IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES INTO THE ECONOMY - Azizova Manzura Ibragimovna (Web of Journals Publishing, 2023)
The definitions of the concept “artificial intelligence” are considered. The impact of artificial intelligence technologies on global economic growth, the labor market, and the financial sector is explored. Both positive aspects and threats caused by their introduction into the economy are analyzed.
Keywords: artificial intelligence; global economic growth; employment; financial sector.